Enterprise application integration: Approaches and platforms to design and implement solutions in the cloud - Rosa-Sequeira, F. (2022)
Nowadays companies have a software ecosystem composed of more than one application to support their business processes. On the Enterprise Application Integration (EAI) field can be found a set of methods, techniques, and tools to integrate them in a synchronous or asynchronous way. In this chapter, we review integration approaches and integration platforms available in the Cloud. We demonstrate the use of an integration platform by means of a case of study for a research outcomes and technological information management integration problem. The proposal addresses Portuguese and international science and research outcomes information management, and corresponding information systems. There are presented problems in interoperability between information systems. A business and technological perspective is provided, including the conceptual analysis and modelling, an integration solution based on a Domain-Specific Language (DSL) and the integration platform to execute the proposed solution. For illustrative purposes, the role and information system needs of a research unit is assumed as the representative case.